The Florida Bull Test 2008-2009 - G. Cliff Lamb (EDIS)
AN228, a 5-page fact sheet by G. Cliff Lamb, reports on this performance test and breeding soundness evaluation conducted in 2008-2009 — procedures, rules and regulations, results, and sale summary. Includes 2009-2010 test dates and a table of individual animal performance. Published by the UF Department of Animal Sciences, October 2009.